Designing accessories - Lau, John (Basics fashion design, 2012)
Designing Accessories explores contemporary techniques that break new boundaries in accessories design, including hand-finishing and machine embellishment techniques. Finally, a detailed explanation of small accessories, essential to the accessories designer, will provide readers with the skills needed to enter the fashion industry.